Prioritising Intentions on the Margins: Effects of Marginally Higher Prioritisation Strategies on Physical Activity Participation - Chatzisarantis, Nikos; Barkoukis, V.; Petridis, P.; Thøgersen-Ntoumani, Cecilie; Ntoumanis, Nikos; Gountas, Sandra; Gountas, J.; Adam, Dimitrios; Hagger, Martin (Human Kinetics, 2016)
Previous research documented that 'extremely high prioritisation' strategies that involved allocation of all resources for time or energy on pursuing goals related to leisure-time physical activity and none of available resources on competing behavioural goals were the most optimal in terms of yielding highest levels of participation in physical activities. This study examined whether a 'marginally higher prioritisation' strategy that involved an intention to invest large but slightly more resources on physical activity than competing behaviours was optimal. In addition, we examined whether linear and quadratic models supported different conclusions about optimal prioritisations strategies. Response surface analyses of a quadratic model revealed that 'marginally higher prioritisation' was the most optimal strategy. In addition, a linear regression model led us to incorrectly reject a 'simultaneous goal pursuit' strategy in favour of an 'extremely high prioritisation' strategy. Findings suggest that prioritisation strategies that 'garner' low opportunity costs are the most optimal.